Families as roommates: Changes in US household size from 1850 to 2000 - Alejandrina Salcedo; Todd Schoellman; Michèle Tertilt (Banco de México, 2010)
The size of the average American household has fallen dramatically - from six in 1850 to three in 2000. To explain this decline we model households as collections of roommates who share the costs of household public goods. If private goods are more income elastic than public goods, as we document in the paper, an increase in income endogenously leads to smaller households. We calibrate the model to match data from 2000. Changing incomes to their 1850 levels, we find that our mechanism can explain 37 percent of the observed reduction in the number of adults per household and 16 percent of the reduction in the number of children.
Keywords: D10; E10; J11; N30; O10; 330; household size; living arrangements; roommates; economies of scale; household public goods; fertility decline; Privater Haushalt; Haushaltsökonomik; Familie; Eltern; Kinder; Einkommen; Konsum; Alleinlebende; Sozialgeschichte; USA